2004
DOI: 10.1212/01.wnl.0000130200.12993.0c
|View full text |Cite
|
Sign up to set email alerts
|

DD genotype of ACE gene is a risk factor for intracerebral hemorrhage

Abstract: Genetic factors may play a role in susceptibility to stroke. The angiotensin converting enzyme (ACE) gene is a candidate gene for two phenotypically different types of stroke affecting small perforating arteries: spontaneous intracerebral hemorrhage (SIH) and ischemic stroke due to small vessel disease (SVD). The authors report evidence that ACE gene DD homozygosity of the I/D polymorphism in intron 16 is an independent risk factor for SIH, and not for SVD stroke, in a Polish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 11 publications
(10 reference statements)
3
39
1
Order By: Relevance
“…[41][42][43][44] ACE I/D polymorphisms have also been extensively studied in several cardiovascular adult diseases, such as thoracic aortic dissection, 45 ischaemic stroke, 13 coronary heart disease, 14,46 left ventricular hypertrophy 47 and intracerebral haemorrhage. [15][16][17][18][19][20] In conclusion, data from the present study suggest that the ACE DD genotype may be a protective factor against IA in a Chinese population. A larger, multicentre study, which is statistically powered to detect differences in the risk of IA between different ACE genotypes, is required in order to confirm the present results.…”
Section: Discussionsupporting
confidence: 51%
“…[41][42][43][44] ACE I/D polymorphisms have also been extensively studied in several cardiovascular adult diseases, such as thoracic aortic dissection, 45 ischaemic stroke, 13 coronary heart disease, 14,46 left ventricular hypertrophy 47 and intracerebral haemorrhage. [15][16][17][18][19][20] In conclusion, data from the present study suggest that the ACE DD genotype may be a protective factor against IA in a Chinese population. A larger, multicentre study, which is statistically powered to detect differences in the risk of IA between different ACE genotypes, is required in order to confirm the present results.…”
Section: Discussionsupporting
confidence: 51%
“…4 Genomic DNA was extracted from peripheral blood using a commercially available kit from Boehringer Mannheim. SERPINA3 polymorphism was studied using polymerase chain reaction restriction fragment length polymorphism method.…”
Section: Methodsmentioning
confidence: 99%
“…However, after excluding the individuals who were receiving ACE inhibitors and adjusting for other variables, the association was no longer statistically significant. 51 In a previous study, the distribution of ACE genotypes and alleles was the same among the controls and patients. 52 It was shown that ACE I/D polymorphism only partially determines the variation in plasma ACE levels, and it is uncertain whether it represents a functional polymorphism; this may explain the inconsistency between the two studies.…”
Section: Angiotensin-converting Enzyme Genementioning
confidence: 84%